Otimização do sistema de multiplicação in vitro por meio do método Scalp e indução do aumento da variabilidade genética pelo uso de mutagênico químico e da transformação genética em bananeira (Musa spp., AAB) - Oliveira, Maria Maiany de (2017)
Banana (Musa spp.) is considered one of the most important fruits in world trade due to its nutritional and economic potential.But although there is a large number varieties on the market, the banana is still affected by many diseases.The application of the method of crosses in this species is very difficult because the majority of cultivated varieties is triploid presenting low fertility. In this case, it is necessary to use biotechnology and its tools applied to non-conventional genetic improvement to develop new varieties that have resistance to their different types of pathogens.This work was carried out with the objective of adapting the technique of obtaining embryogeniccallus of banana by means of the Scalp method in cultivars Brazilian Maçã and Pacovan, adjusting the processes of induction of meristematic structures and multiplication of shoots and induce increased genetic variability by in vitro mutagenesis using the chemical agent ethylmethanesulfonate and, of the genetic transformation by the bombardment of microparticles. Was evaluated the callus formation, the effect of mutagenic in the in vitro cultivation of shoots and the effects of genetic transformation on shoot resistance in selection medium containing the herbicide Imazapyr. The results showed that the merystematic structures obtained have the capacity to origin callus with only one month of cultivation, and both cultivars developed friable callus with average values above 90%.The efficiency of this method was evidenced by the high capacity of induction of friable callus in the two evaluated cultivars but also by the rapidity in the process of obtaining calluses, being the first study of adaptation of the methodology for Brazilian banana cultivars.On the other hand, the evaluation of the mutation induction allowed to conclude that the survival and the capacity of bud formation decreased as a function of the increase of the concentration and the immersion time in the ethylmethanesulfonate.The surviving plants underwent a sorting with the fusaric acid selective agent in which it was possible to regenerate in vitro plants of the cultivars submitted to treatment with the mutagen and to select possible mutants with fusaric acid resistance for cultivarsMaçã and Pacovan.And the genetic transformation method proved efficient in the regeneration of shoots resulting in high values of survival and multiplication, where possible transgenic plants of banana cv. Maçã were obtained after selection of resistance to the herbicide.Therefore, it is concluded that all the material produced, both in the mutagenic phase and in the genetic transformation, presents a greater genetic variability potentially applicable to the banana improvement.